Author 
Message 
TAGS:

Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 47983

For the infinite series a1, a2, ..., an, an=a(n−1)+n, and a1=1. If n>4
[#permalink]
Show Tags
21 Nov 2016, 02:46
Question Stats:
45% (02:18) correct 55% (02:10) wrong based on 133 sessions
HideShow timer Statistics



Senior CR Moderator
Status: Long way to go!
Joined: 10 Oct 2016
Posts: 1394
Location: Viet Nam

Re: For the infinite series a1, a2, ..., an, an=a(n−1)+n, and a1=1. If n>4
[#permalink]
Show Tags
21 Nov 2016, 05:33
Bunuel wrote: For the infinite series \(a_1\), \(a_2\), ..., \(a_n\), \(a_n=a_{(n−1)}+n\), and \(a_1=1\). If n>4, is an an odd integer?
(1) \(a_{(n−1)}\) is even
(2) \(a_{(n−4)}\) is odd You mean " is \(a_n\) an odd integer?"? \(a_{1}=1\) \(a_{2}=a_{1}+2=3\) \(a_{3}=a_{2}+3=6\) \(a_{4}=a_{3}+4=10\) \(a_{5}=a_{4}+5=15\) \(a_{6}=a_{5}+6=21\) \(a_{7}=a_{6}+7=28\) \(a_{7}=a_{6}+7=28\) Solution 1:(1) \(a_{n1}\) is even so \(a_{n1}=a_{n}n\) is even, so \(a_n\) could be even or odd. Insufficient (2) \(a_{n4}\) is odd so \(a_{n4}=a_{n3}(n3)=a_{n2}(2n5)=a_{n1}(3n6)=a_n(4n6)\) is odd, so \(a_n\) is odd. Sufficient The answer is B. Solution 2:\(a_{1}=1\) \(a_{2}=a_{1}+2=1+2\) \(a_{3}=a_{2}+3=1+2+3\) \(a_{4}=a_{3}+4=1+2+3+4\) \(a_{k}=1+2+ \dots + k=\frac{k(k+1)}{2}\) (1) \(a_{n1}=\frac{n(n1)}{2}\) is even, so \(n(n1)\) is divisible by 4. Hence, \(n=4k\) or \(n1=4k\). If \(n=4k\)we have \(a_n=\frac{n(n+1)}{2}=\frac{4k(4k+1)}{2}=2k(4k+1)\) is even. If \(n1=4k\) , we have \(a_n=\frac{n(n+1)}{2}=\frac{(4k+1)(4k+2)}{2}=(4k+1)(2k+1)\) is odd. Insufficient. (2) \(a_{n4}=\frac{(n4)(n3)}{2}\) is odd, so \((n4)(n3)\) is divisible by 2 and not by 4. Hence, \(n4=4k+2\) or \(n3=4k+2\). If \(n4=4k+2 \iff n=4k+6\), we have \(a_n=\frac{n(n+1)}{2}=\frac{(4k+6)(4k+7)}{2}=(2k+3)(4k+7)\) is an odd integer. If \(n3=4k+2 \iff n=4k+5\), we have \(a_n=\frac{n(n+1)}{2}=\frac{(4k+5)(4k+6)}{2}=(4k+5)(2k+3)\) is an odd integer. Sufficient.
_________________
Actual LSAT CR bank by Broall
How to solve quadratic equations  Factor quadratic equations Factor table with sign: The useful tool to solve polynomial inequalities Applying AMGM inequality into finding extreme/absolute value
New Error Log with Timer



Senior SC Moderator
Joined: 14 Nov 2016
Posts: 1322
Location: Malaysia

For the infinite series a1, a2, ..., an, an=a(n−1)+n, and a1=1. If n>4
[#permalink]
Show Tags
06 Feb 2017, 18:48
Bunuel wrote: For the infinite series \(a_1\), \(a_2\), ..., \(a_n\), \(a_n=a_{n−1}+n\), and \(a_1=1\). If n>4, is \(a_n\) an odd integer?
(1) \(a_{n−1}\) is even
(2) \(a_{n−4}\) is odd Official solution from Veritas Prep. As with most sequence problems, your most effective strategy is typically to list out the first few terms of the sequence to see if you can establish a pattern or trend. Here you will find: First Term: 1 (Odd) Second Term: 1 + 2 = 3 (Odd) Third Term: 3 + 3 = 6 (Even) Fourth Term: 6 + 4 = 10 (Even) Fifth Term: 10 + 5 = 15 (Odd) Sixth Term: 15 + 6 = 21 (Odd) Seventh Term: 21 + 7 = 28 (Even) Eighth Term: 28 + 8 = 36 (Even) From that, you should see the pattern that the evenness/oddness of terms in this sequence progresses in pairs: Odd, Odd, Even, Even, Odd, Odd, Even, Even... And you can see the reason why. When you're at an even number and add an odd, you of course get an odd sum. And since you just added an odd, the next integer will be even so you'll be adding an even to an odd to get odd. Having just added an even, the next number will be odd so you'll have odd + odd, which is even, and the next number up to add is even. Then the cycle will repeat. This means, then, that statement 1 is not sufficient. If you're on an even term for \(a_{n−1}\), the pattern shows that it could be the first of two consecutive evens (in which case an would be the second even), or that it could be the second (in which case an would be odd). Statement 2, however, is sufficient. Given the list Odd, Odd, Even, Even, Odd, Odd, Even, Even, Odd, Odd, Even, Even, Odd, Odd..., you should see that if you're on an Odd value and move four spaces away, you'll always land on another odd value. Therefore, statement 2 is sufficient and the correct answer is B.
_________________
"Be challenged at EVERY MOMENT."
“Strength doesn’t come from what you can do. It comes from overcoming the things you once thought you couldn’t.”
"Each stage of the journey is crucial to attaining new heights of knowledge."
Rules for posting in verbal forum  Please DO NOT post short answer in your post!
Advanced Search : https://gmatclub.com/forum/advancedsearch/



Intern
Joined: 15 Jan 2014
Posts: 22
Location: India
Concentration: Technology, Strategy
GPA: 2.5
WE: Information Technology (Consulting)

For the infinite series a1, a2, ..., an, an=a(n−1)+n, and a1=1. If n>4
[#permalink]
Show Tags
06 Feb 2017, 20:07
Statement 1 : \(a_{(n1)}\) is even.
Given : \(a_n\)  \(a_{(n1)}\) = n
\(a_n\) = n + \(a_{(n1)}\)
\(a_n\) = Odd + Even > Odd if n is odd \(a_n\) = Even + Even > Even if n is Even Not Sufficient .
Statement 2 : \(a_{(n−4)}\) is odd
Given : \(a_n\)  \(a_{(n1)}\) = n
So now we need to relate \(a_{(n−4)}\) with \(a_{(n)}\)
\(a_{(n−3)}\)  \(a_{(n−4)}\) = n (1) \(a_{(n−2)}\)  \(a_{(n−3)}\) = n (2) \(a_{(n−1)}\)  \(a_{(n−2)}\) = n (3) \(a_{(n)}\)  \(a_{(n−1)}\) = n (4)
(1) + (2) +(3)+(4)
\(a_{(n−3)}\)  \(a_{(n−4)}\) = n (1) \(a_{(n−2)}\)  \(a_{(n−3)}\) = n (2)  \(a_{(n−2)}\)  \(a_{(n−4)}\) = 2n \(a_{(n−1)}\)  \(a_{(n−2)}\) = n (3)  \(a_{(n−1)}\)  \(a_{(n−4)}\) = 3n \(a_{(n)}\)  \(a_{(n−1)}\) = n (4)  \(a_{(n)}\) \(a_{(n−4)}\) = 4n 
Now ,
\(a_{(n)}\) = 4n + \(a_{(n−4)}\) \(a_{(n)}\) = Even + Odd = Odd > Sufficient
Answer B.



Intern
Joined: 23 Jan 2017
Posts: 7
Location: Canada
GPA: 3.4

Re: For the infinite series a1, a2, ..., an, an=a(n−1)+n, and a1=1. If n>4
[#permalink]
Show Tags
07 Feb 2017, 16:39
pranjal123 wrote: Statement 1 : \(a_{(n1)}\) is even.
Given : \(a_n\)  \(a_{(n1)}\) = n
\(a_n\) = n + \(a_{(n1)}\)
\(a_n\) = Odd + Even > Odd if n is odd \(a_n\) = Even + Even > Even if n is Even Not Sufficient .
Statement 2 : \(a_{(n−4)}\) is odd
Given : \(a_n\)  \(a_{(n1)}\) = n
So now we need to relate \(a_{(n−4)}\) with \(a_{(n)}\)
\(a_{(n−3)}\)  \(a_{(n−4)}\) = n (1) \(a_{(n−2)}\)  \(a_{(n−3)}\) = n (2) \(a_{(n−1)}\)  \(a_{(n−2)}\) = n (3) \(a_{(n)}\)  \(a_{(n−1)}\) = n (4)
(1) + (2) +(3)+(4)
\(a_{(n−3)}\)  \(a_{(n−4)}\) = n (1) \(a_{(n−2)}\)  \(a_{(n−3)}\) = n (2)  \(a_{(n−2)}\)  \(a_{(n−4)}\) = 2n \(a_{(n−1)}\)  \(a_{(n−2)}\) = n (3)  \(a_{(n−1)}\)  \(a_{(n−4)}\) = 3n \(a_{(n)}\)  \(a_{(n−1)}\) = n (4)  \(a_{(n)}\) \(a_{(n−4)}\) = 4n 
Now ,
\(a_{(n)}\) = 4n + \(a_{(n−4)}\) \(a_{(n)}\) = Even + Odd = Odd > Sufficient
Answer B. Anyone have a suggestion on what I should study to understand this question? The question doesn't make sense to me, and the answers don't help. I clearly need to build some foundation on this topic. Thanks!



Intern
Joined: 15 Jan 2014
Posts: 22
Location: India
Concentration: Technology, Strategy
GPA: 2.5
WE: Information Technology (Consulting)

For the infinite series a1, a2, ..., an, an=a(n−1)+n, and a1=1. If n>4
[#permalink]
Show Tags
07 Feb 2017, 17:03
funnypanks wrote: pranjal123 wrote: Statement 1 : \(a_{(n1)}\) is even.
Given : \(a_n\)  \(a_{(n1)}\) = n
\(a_n\) = n + \(a_{(n1)}\)
\(a_n\) = Odd + Even > Odd if n is odd \(a_n\) = Even + Even > Even if n is Even Not Sufficient .
Statement 2 : \(a_{(n−4)}\) is odd
Given : \(a_n\)  \(a_{(n1)}\) = n
So now we need to relate \(a_{(n−4)}\) with \(a_{(n)}\)
\(a_{(n−3)}\)  \(a_{(n−4)}\) = n (1) \(a_{(n−2)}\)  \(a_{(n−3)}\) = n (2) \(a_{(n−1)}\)  \(a_{(n−2)}\) = n (3) \(a_{(n)}\)  \(a_{(n−1)}\) = n (4)
(1) + (2) +(3)+(4)
\(a_{(n−3)}\)  \(a_{(n−4)}\) = n (1) \(a_{(n−2)}\)  \(a_{(n−3)}\) = n (2)  \(a_{(n−2)}\)  \(a_{(n−4)}\) = 2n \(a_{(n−1)}\)  \(a_{(n−2)}\) = n (3)  \(a_{(n−1)}\)  \(a_{(n−4)}\) = 3n \(a_{(n)}\)  \(a_{(n−1)}\) = n (4)  \(a_{(n)}\) \(a_{(n−4)}\) = 4n 
Now ,
\(a_{(n)}\) = 4n + \(a_{(n−4)}\) \(a_{(n)}\) = Even + Odd = Odd > Sufficient
Answer B. Anyone have a suggestion on what I should study to understand this question? The question doesn't make sense to me, and the answers don't help. I clearly need to build some foundation on this topic. Thanks! Well,As the question tags says "Number Properties" so you need to study Number properties topic. As you can see question test 2 properties here : 1: outcome of adding ODD and EVEN numbers. 2: Difference between 2 consecutive numbers is constant. In general, for any series based question you need to find the pattern for small set of numbers. As in this question , Plug n=7 you will get \(a_{7}\)  \(a_{6}\) = n On plugging n=6 \(a_6\)  \(a_{5}\) = n And here you have it . 2 numbers have a common difference. With this you can see the pattern in above 2 equation and move forward . OR Just to make things more clearer Put n =11 everywhere in the question and then solve it. Hope this helps



NonHuman User
Joined: 09 Sep 2013
Posts: 7754

Re: For the infinite series a1, a2, ..., an, an=a(n−1)+n, and a1=1. If n>4
[#permalink]
Show Tags
28 Jul 2018, 08:34
Hello from the GMAT Club BumpBot! Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up  doing my job. I think you may find it valuable (esp those replies with Kudos). Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________
GMAT Books  GMAT Club Tests  Best Prices on GMAT Courses  GMAT Mobile App  Math Resources  Verbal Resources




Re: For the infinite series a1, a2, ..., an, an=a(n−1)+n, and a1=1. If n>4 &nbs
[#permalink]
28 Jul 2018, 08:34






